Peacetime Maritime Law Enforcement by Warships - Ma, Deyi; Zhou, Yanlin (Journal on the use of force and international law, 2024)
The scope and methods of maritime law enforcement by warships in peacetime are evolving, triggering international armed conflicts. A core issue is how to distinguish between law enforcement activities and military operations at sea. The construction of an international law regime for peacetime maritime law enforcement by warships will help to reduce the incidence of armed conflicts. This is consistent with the need for a strict interpretation of the principle of prohibiting the threat or use of force under the United Nations Charter. Based on the principles of prohibiting the use of force, the peaceful use of the seas and considerations of good faith, it is possible to establish a stable international legal system for maritime law enforcement by warships. The system would be based on the United Nations Convention on the Law of the Sea (UNCLOS) and would operate primarily through implementing agreements as its main model.